Лімфорея та набряковий синдром у поопераційний період у хворих, оперованих на щитоподібній залозі - Безруков, О. Ф.; Клішевич, І. Б.; Паламарчук, В. О. (Clinical Endocrinology and Endocrine Surgery, 2012)
The purpose of our work was to analize the complex of preventive actions against oedematous syndrome and lymphorrhea in a postoperative period during the operation on a thyroid. The analysis of work proved that careful haemostasis,and usage of 0,1% solution of "L-Lysine Aescinat" and "Lioton Gel" considerably reduces the risk of lymphorrhea and diminishes the display of oedematous syndrome in a postoperative period. It is offered the original method of filimng of postoperative cavities at massive lymphorrhea.